Nab-paclitaxel: A revolution in the nano-therapeutic approach to IDH-wildtype glioblastoma - Siddiqui, Maria Fareed; Hassan, Amber; Tahir, Muzna; Okal, Fahad; Baeesa, Saleh; Alkhotani, Alaa; Jasaniah, Zayd; Fallatah, Ahmad; Faizo, Eyad; Mirdad, Dahlia; Althaqafi, Bashayer A.; Kurdi, Maher (Folia Neuropathologica, 2025)
Paclitaxel (PTX) is a potent chemotherapy drug commonly used to treat various solid tumours, including breast and ovarian cancers. However, its effectiveness in treating IDH-wildtype glioblastoma has been limited due to challenges crossing the blood-brain barrier (BBB). Glioblastoma remains one of the most difficult cancers to treat, with a median survival of 15 months from diagnosis. Recent advancements in nanotechnology have led to innovative PTX delivery systems that enhance its bioavailability and enable targeted brain therapy. These include nanoparticles composed of biocompatible materials that enhance drug solubility and targeting while addressing BBB permeability. Examples include albumin-bound PTX (Abraxane), self-assembled nanoparticles from natural bioactive molecules, poly(lactic-co-glycolic acid) (PLGA)-based nanoparticles, and hydrophilic nano-prodrugs, each showing promise in enhancing the therapeutic impact of PTX. These systems utilize biocompatible nanoparticles that enhance drug solubility, targeting, and BBB permeability. Numerous ongoing clinical trials and preclinical studies are exploring the efficacy of these nanocarrier systems in overcoming drug resistance and improving patient outcomes. The latest advancements in PTX-based nanotherapeutics for glioblastoma focus on overcoming the BBB, developing nanoparticle delivery systems, and evaluating the clinical significance of these developments.